Tradisi Malam Satu Suro sebagai Wujud Implementasi Kerukunan Masyarakat Desa Tambibendo Kabupaten Kediri - Anggi Dian Pramitha Sari; Bagus Wahyu Setiawan (Universitas Sebelas Maret, 2025)
This study aims to describe the implementation of community harmony in Tambibendo Village, Kediri Regency in the one suro night tradition. This research discusses several things regarding the meaning of the one suro night tradition for the people of Tambibendo Village, as well as the implementation of harmony from the celebration of the one suro night tradition. The one suro night tradition is one of the sacred night traditions performed by the Javanese people every year at the beginning of the Muslim new year. This is also a tradition in Tambibendo Village, the one suro night tradition is one of the customs that is still maintained in the village area. This tradition is believed to strengthen the bonds of kinship and to preserve ancestral traditions that are a bit forgotten. This is in line with the implementation of the one suro night tradition, the people of Tambibendo Village hold an activity called Kenduri. Therefore, in this research the method used is qualitative based on literature research. Qualitative descriptive research aims to describe, explain, and answer problems for further study by studying as many individuals, groups or events as possible. The data used to strengthen this research is using books, journals, to previous research as well as pictures documenting the one suro night tradition event in Tambibendo Village which will be held in 2021.